2022
DOI: 10.3390/buildings12101602
|View full text |Cite
|
Sign up to set email alerts
|

Optimization for the Model Predictive Control of Building HVAC System and Experimental Verification

Abstract: This article presents an optimized prediction model of building dynamic HVAC system load, which simplifies the input parameters of the model while meeting the accuracy requirements of the prediction results. The model was established using the open-source Modelica-based building library, and the linear aggregation method was used to establish the model. A reduced-order model was developed, and the accuracy of the simplified and reduced-order models was verified. A control strategy was constructed using the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The unknown parameters of the model (model coefficients) are estimated using measured data and parameter estimation techniques. Parameter identification of RC models can be computationally expensive, and different methods, such as model reduction, are often used to improve the computational cost [20,51]. Some examples of studies applying the gray-box modeling approach can be found in [52][53][54][55][56][57][58].…”
Section: Mpc Paradigmsmentioning
confidence: 99%
“…The unknown parameters of the model (model coefficients) are estimated using measured data and parameter estimation techniques. Parameter identification of RC models can be computationally expensive, and different methods, such as model reduction, are often used to improve the computational cost [20,51]. Some examples of studies applying the gray-box modeling approach can be found in [52][53][54][55][56][57][58].…”
Section: Mpc Paradigmsmentioning
confidence: 99%
“…A multitude of techniques has been devised for optimizing HVAC systems, which can be broadly classified into three categories: artificial intelligence (AI), simulation, and regression analysis. Simulation tools like DOE-2, ESP-r [10], TRNSYS [11], EnergyPlus and ACO [12] are used to estimate CL when complete building data is accessible. Accurately measuring different building parameters, however, presents practical challenges [13].…”
Section: Introductionmentioning
confidence: 99%
“…Si et al [15] optimised the method for HVAC load prediction. The proposed prediction model was simplified and reduced order for time-efficient simulation and control, by integrating an equivalent envelope structure, heat gain calculation linearization and building pre-processing module in OpenModelica.…”
mentioning
confidence: 99%